2010
DOI: 10.1203/00006450-201011001-00485
|View full text |Cite
|
Sign up to set email alerts
|

485 Evaluation of Oral Hygiene Habits in a Portuguese Primary School Children Population

Abstract: Primary prevention of cardiovascular diseases and promotion of active lifestyle should start early. Blood pressure (BP) in childhood correlates with BP in adulthood. The knowledge about children's physical activity influence on BP is limited. Aims:To analyse the relation between physical activity (PhyA) and time of "screen-activities" (ST) performed by children and BP.Methods: 428 children were enrolled, provided parent's consent. Measurements: BP: systolic (syst) and diastolic (diast) Z-score, pulse pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Omega-3-polyunsaturated fatty acids decrease the size of the avascular area, and this protective effect may be mediated in part via suppression of TNFa (Connor et al 2007). Markers of inflammation also appear to be associated with ROP inhuman studies (Lavoie et al 2010). Over the first three postnatal weeks, the systemic levels ofeight cytokines and chemokines were different in infants with ROP compared with controls, and co-occurrence of immaturity, proinflammatory cytokines, and neonatal systemic inflammation is associated with increased risk for ROP.…”
Section: Key Factors That Influence Retinal Vascular Developmentmentioning
confidence: 99%
“…Omega-3-polyunsaturated fatty acids decrease the size of the avascular area, and this protective effect may be mediated in part via suppression of TNFa (Connor et al 2007). Markers of inflammation also appear to be associated with ROP inhuman studies (Lavoie et al 2010). Over the first three postnatal weeks, the systemic levels ofeight cytokines and chemokines were different in infants with ROP compared with controls, and co-occurrence of immaturity, proinflammatory cytokines, and neonatal systemic inflammation is associated with increased risk for ROP.…”
Section: Key Factors That Influence Retinal Vascular Developmentmentioning
confidence: 99%
“…The potential neurotoxic effect of inflammation and the role in the etiology of white matter disease in preterm infants has been described in detail [ 43 , 44 ]. Non-infectious inflammation in preterm infants has been associated with several invasive therapies such as mechanical ventilation [ 45 ], parenteral nutrition [ 46 , 47 ] and oxygen supplementation [ 46 , 48 ]. Cai et al demonstrated in an animal model of neonatal brain injury the detrimental effect of intracerebral injection of the pro-inflammatory cytokine Interleukin-1b in the absence of infection [ 49 ].…”
Section: Discussionmentioning
confidence: 99%